Evaluation of distributors during the commercialization of innovative production by industrial enterprise. - Bilovodska, Olena (Scientific Journal of Bielsko-Biala School of Finance and Law, 2019)
Distributors who operate on the channel and do the same job, do not always make it the same: relationships with some of them will always be more beneficial than others. So it is necessary to analyze each aspect of their relationship with each distributors. It may become clear that the distributor, through which the largest volumes of goods are sold, in fact, almost does not bring the profit to the producer, and a small trading company, on the contrary, has a significant potential. Therefore, it is necessary to constantly optimize work with distributors, to evaluate them both from the standpoint of the commodity producer and the consumer of the goods. On the basis of improved criteria system of distributors during the commercialization of innovative production by chemical industry’s enterprise are evaluated. For each assessment criterion, the appropriate scale and formula for calculating the integral estimate are determined. The proposed approach deepens the existing theoretical and practical approaches in marketing distribution policy.